IMPACT ANALYSIS OF THE ERUPTION OF MOUNT TAMBORA TO TEMPERATURE AND PRECIPITATION VARIABILITY IN INDONESIA USING MPI-ESM SIMULATION MODEL OUTPUT - Camelia (NIM : 12814035) , Hana
The impact of the eruption of Mount Tambora in 1815 on meteorological parameters in Indonesia is not widely known because of the absence of weather observation data at that time. In this study we examine the impact of the eruption in Indonesia by using one of the Max-Planck Institute Earth System Model (MPI-ESM) simulation scenarios which previously selected by comparing it to the proxy data 𝛿18𝑂 of the Porites sp. coral. This study examines the impacts of temperature and precipitation variations in the period of June-July-August (JJA) and December-February-January (DJF). The 𝛿18𝑂 data is compared with the reanalysis data to see if the data 𝛿18𝑂 is capable of recording temperature and precipitation changes or not. The model data is then compared with the data 𝛿18𝑂 to see the consistency between them. Consistency analysis is performed to select the most representative model scenario. In addition, a comparison of the Nino 3.4 index from proxy reconstruction data with the Nino 3.4 index which was derived from the model to analyze the effect of ENSO on the occurrence and after eruption of Mount Tambora in 1815. After that, there is impact analysis of the eruption of Mount Tambora in 1815 temporally and spatially. The model simulation shows well consistency over surface temperature during June-July-August (JJA), but has not been able to accurately describe the precipitation anomaly after the eruption. Based on the simulation results, the eruption of Mount Tambora in 1815 caused a decrease in temperature of 0.4-1Ã‚Â°C in Indonesia in 1816-1817 and the temperature returned to normal in the years after.